Cohosts with efficient host-to-emitter energy transfer for stable blue phosphorescent organic light-emitting diodes. Issue 48 (22nd November 2021) - Ihn, Soo-Ghang; Kwon, Eun Suk; Jung, Yongsik; Kim, Jong Soo; Nam, Sungho; Kim, Joonghyuk; Kim, Sangmo; Jeon, Soon Ok; Chung, Yeon Sook; Park, Sangho; Huh, Dal Ho; Kim, Hyun Jung; et al.
Abstract : We present a high-performance blue phosphorescent organic light-emitting diode exhibiting a low operating voltage (4.1 V), high external quantum efficiency (23.4%, at 500 cd m −2 ) with a low efficiency roll-off (4.7%), and a long operation lifetime (time at which the luminance reaches 95% of its initial value, LT95 = 232 h). Abstract : We present a high-performance blue phosphorescent organic light-emitting diode exhibiting a low operating voltage (4.1 V), high external quantum efficiency (23.4%, at 500 cd m −2 ) with a low efficiency roll-off (4.7%), and a long operation lifetime (time at which the luminance reaches 95% of its initial value, LT95 = 232 h). These are mainly attributed to a well-developed exciplex-forming cohost composed of judiciously selected component hosts. The cohost provides low injection barriers and stable transport for both positive and negative charges, excellent charge balance, and finely tuned exciplex energy for efficient host-to-emitter energy transfer.